Gingival Enlargement as Initial Manifestation of Acute Myeloid Leukemia : A Case Report - Suparthika, Ni Putu Radha Premaiswari (Jurnal Health Sains, 2025)
Acute myeloid leukemia (AML) is a disease of hematopoietic stem cells in the bone marrow that proliferates and differentiates abnormally. AML can develop aggressively and cause a variety of complaints due to bone marrow suppression and symptoms of inflection to individual organs. Symptoms and signs of AML can be caused due to the suppression of the bone marrow resulting in ineffective erythropoesis. The oral cavity can show the first clinical manifestations of leukemia. Individuals with leukemia may show lesions such as enlarged gums. Case Presentation: A 31-year-old female patient was referred from the Dental Polyclinic of Tabanan Hospital with complaints of enlarged gums since 1 month ago. Enlargement occurs in the gums behind which incisors enlarge rapidly. Other complaints include fever up and down, weakness, bleeding through the anus. The results of the Complete Blood test found a very high WBC value, with bicytopenia, with BMP examination showing AML with M4 morphology. Conclusions: In a 31-year-old female patient, gum enlargement was found as an early manifestation of acute myeloid leukemia (AML) accompanied by constitutional symptoms such as fever, weakness, spleenomegaly. Clinical manifestations of AML can include symptoms of suppression of the bone marrow by malignant cells, and infiltration into organ systems. Oral manifestations of AML can include enlargement of the gums, discoloration of the mucous membranes to bluish or pale, ulcers, erosion, bleeding, ecchymosis, which can be mistaken for manifestations of other diseases.